Perlindungan Hak Korban dalam Perspektif HAM Studi Kasus Putusan Nomor 1/Pid.Sus/2023/Pt BDG Tentang Binomo Berkedok Investasi - Nindya Septica Andari (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2024)
This research examines the juridical protection provided by the government to victims of illegal online investment crimes as regulated in Article 378 of the Criminal Code (KUHP) and Article 28 paragraph (1) of Law Number 19 of 2016 concerning Amendments to the Law Number 11 of 2008 concerning Information and Electronic Transactions. Apart from that, the provisions on criminal acts of gambling regulated in Article 303 bis Paragraph (1) of the Criminal Code are also used as a reference in this research. This research analyzes the typology of victims and the factors that cause illegal investments both online and conventional. Based on this analysis, researchers identified three types of factors that influence victims of illegal investment, namely Latent or Predisposed Victims (victims influenced by economic factors), Participating Victims (victims with low education), and False Victims (victims due to consumer behavior). In this context, researchers recommend the need for more detailed legal updates regarding online investment regulations. This update aims to strengthen the protection of the rights of investors and society as a whole, so that they feel more confident and safe in making investments. With more comprehensive regulations, the government can provide better protection for victims of illegal investment crimes and prevent illegal practices that harm society.